Anaesthetic management of a child with Wolf–Hirschhorn syndrome - Priyanka Das; Shalini Subramanian (Journal of Clinical and Scientific Research)
Wolf–Hirschhorn syndrome (WHS) is a malformation syndrome that is characterised by a partial deletion of the short arm of chromosome 4 and is known to occur in about one per 50,000 births. Ophthalmic manifestations are common in patients with WHS, who often require corrective surgery under general anaesthesia. Managing the airway, titration of the anaesthetic medications while vigilant monitoring and controlling the haemodynamics during the surgery can be difficult. Further, presence of various anomalies, concurrent seizures, predisposition to cardiac failure and post-operative occurrence of malignant hyperthermia pose anaesthetic challenges in patients with WHS. We present the case of an 11-month-old child with WHS posted for multiple ophthalmological procedures and the challenges faced while administering anaesthesia for the same.